Financial Stress-Test of the Palm Oil Industry: Bankruptcy Prediction Using the Modified Altman Z-Score During the Downturn Phase - Harke Revo Leonard Polii; Sandra J.R. Kainde; Rifal Richard Pangemanan (Economics and Digital Business Review, 2026)
This study aims to predict the bankruptcy potential of Plantation Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) during the critical downturn cycle of 2017-2019. This period serves as a stress-test window following the commodity boom. Employing a descriptive quantitative approach, the research analyzes secondary data from 10 companies selected through purposive sampling. The primary analytical tool is the Modified Altman Z-Score model. The results indicate severe financial distress within the sector due to price volatility and aggressive downstreaming policies. Specifically, out of the 10 sampled companies, only 1 company was classified as "Healthy" (Z > 2.60), 1 company was identified as "Vulnerable" or in the grey area (1.10 < Z < 2.60), and 8 companies were predicted to be "Bankrupt" (Z < 1.10). These empirical findings suggest a critical vulnerability in the plantation sector, highlighting an urgent need for financial restructuring and strategic management improvements to navigate post-boom challenges and ensure long-term sustainability. Keywords: Bankruptcy Prediction, Modified Altman Z-Score, Plantation Sub-Sector, Financial Distress.